Insight into the Katari-Lago Menor Basin aquifer, Lake Titicaca-Bolivia, inferred from geophysical (TDEM), hydrogeological and geochemical data. (April 2020) - Flores Avilés, Gabriela Patricia; Descloitres, Marc; Duwig, Céline; Rossier, Yvan; Spadini, Lorenzo; Legchenko, Anatoly; Soruco, Álvaro; Argollo, Jaime; Pérez, Mayra; Medinaceli, Waldo
Abstract: The increasing demand for water and irrigation in the semi-arid Bolivian Altiplano requires a better knowledge of the available resources, particularly groundwater. The aim of this study is to provide a first insight into the hydrogeological structure (0–200 m deep) and groundwater dynamics of the Katari-Lago Menor Basin aquifer located between the Eastern Cordillera and Lake Titicaca, Bolivia. This aquifer is studied using geophysical data (a total of 187 Time Domain Electromagnetic (TDEM) soundings), piezometric data (97 groundwater level measurements) and geochemical data (52 groundwater samples), combined with geological, lithological and topographical information. The results allowed identifying stratigraphic models consistent with the Quaternary sediments being hydraulically connected and behaving as a single regional basin-aquifer. This basin-aquifer is delimited by the most ancient lake invasions towards the southern, western and northern sides and by the lower limit of rock glaciers towards the eastern side. A large portion of the aquifer presents an unconfined behaviour varying from 50 to 150 m while the confined portion varies from 100 to 150 m. Groundwater flow within the Katari and Lago Menor Basin aquifer is composed of several interconnected groundwater flow systems. The main groundwater flow system starts in the high mountain ranges of the Eastern Cordillera, follows the topographic Piedmont gradient (NE to SW) and discharges in a series of wetlands. This multidisciplinary approach proved to be an appropriate method to derive a consistent picture of the hydrogeological functioning of the Katari-Lago Menor Basin aquifer. Highlights: Performance of a groundwater basin-scale multidisciplinary study. TDEM surveys were efficient to investigate the structure of a basin-scale aquifer. Continuity of Quaternary layers behaving hydraulically as a single aquifer. 3D schematic structure and dynamics of a major aquifer in the Bolivian Altiplano. Basis for the development of a 3D numerical groundwater model.